306 Nationwide Readmission Rates and Costs for Patients With Surgical Evacuation of Nontraumatic Subdural Hematomas: Part 1—Craniotomy. (1st March 2022) - Shaftel, Kelly T.; Cole, Tyler S.; Jubran, Jubran H.; Schriber, Tyler; Little, Andrew S.
Abstract : INTRODUCTION: Despite patients experiencing high recurrence and readmission rates after surgical management of nontraumatic subdural hematomas (SDHs), few studies have examined the causes and predictors of unplanned readmissions in this population on a national scale. METHODS: Using the Nationwide Readmissions Database, we identified patients who underwent craniotomy for nontraumatic SDH evacuation (2010-2015) using a retrospective cohort observational study design. National estimates and variances within the cohort were calculated after stratifying, hospital clustering, and weighting variables. RESULTS: Among 49, 013 patients, 10, 643 (21.7%) had at least 1 readmission within 30 days of their index treatment and 38, 370 (78.3%) were not readmitted. Annual readmission rates did not change during the study period (P = 0.74). The most common primary causes of 30-day readmissions were recurrent SDH (37.1%), venous thromboembolism (12.9%), and delayed hyponatremia and SIADH (syndrome of inappropriate antidiuretic hormone secretion) (12.8%). Comorbidities that independently predicted readmission included congestive heart failure, chronic obstructive pulmonary disease, coagulopathy, diabetes mellitus, liver disease, lymphoma, fluid and electrolyte disorders, metastatic cancer, peripheral vascular disease, psychosis, and renal failure (P = 0.03). Household income in the 51st-75th percentile was associated with a decreased risk of readmission. CONCLUSION: National trends in 30-day readmission rates after nontraumatic SDH treatment via craniotomy provide quality benchmarks that can be used to drive quality improvement efforts on a national level.